Correlation Between Stress and Recurrent Aphthous Stomatitis on Bank Employees in Tulungagung, East Java: An Observational Analytic - Herlambang Prehananto; Istiati; Salsabila Zahro (TALENTA, 2023)
Recurrent Aphthous Stomatitis (RAS) is a prevalent oral disease that detrimentally impacts the quality of life for those affected. One of the several factors that can trigger the emergence of RAS is stress. Psychological stress can adversely affect health and decrease the immune system. Studies in the field of Psychoneuroimmunology have shown the relationship between human behaviour, nerve function, and psychological stress, which can potentially act as a cause of disease and reduce the immunity of the oral mucosa. Therefore, this study aimed to determine the correlation between stress and the incidence of Recurrent Aphthous Stomatitis on bank employees in Tulungagung, East Java. It is an observational analytic study with a cross-sectional approach, involving male bank employees with a marketing position, aged between 27 and 40 years. Data were analyzed and interpreted using the Chi-square test with a nominal variable data scale. The results showed that the asymp. value sig (2-sided) is 0.000, indicating a significant relationship. In conclusion, there is a relationship between stress and Recurrent Aphthous Stomatitis. Â